DIKLAT, KEMAMPUAN DAN KINERJA - Nurdiansyah, Nurdiansyah; Andri, Seno; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2018)
Training, Ability and Performance. This study aims to determine the effect of training on performance, the influence of the ability of employees on employee performance and the influence of training and employee ability on the performance of employees of the Office Immigration Class I Pekanbaru. The method used is descriptive and quantitative method. A sample of 71 people from 127 employees of Immigration Office Class I Pekanbaru with random sampling technique. Techniques of collecting questionnaire data, observation and interview. Data analysis using multiple linear regression. The result of the research shows that partially known variables of training have a significant effect on employee performance. Partially known working ability variables have a significant effect on employee performance. It is simultaneously known that the variables of training and work ability have a significant effect on the performance of the employees at the First Class Immigration Office of Pekanbaru. This indicates with the provision of training and training will improve the ability of employees and will have an impact on improving the performance of these employees.